5,9,11-Trihydroxy-2,2-dimethyl-10-(30-methyl-20-butenyl)-3-(2”-methyl-3”-butenyl)pyrano[2,3-a]xanthen-12(2H)-one from the Stem Bark of Calophyllum pseudomole - Tanjung, Mulyadi (MDPI AG, Basel, Switzerland, 2016)
5,9,11-Trihydroxy-2,2-dimethyl-10-(30-methyl-20-butenyl)-3-(2”-methyl-3”-butenyl)-pyrano[2,3-a]xanthen-12(2H)-one (1) was isolated from the stem bark of Calophyllum pseudomole. The structure of 1 was established by spectroscopic analysis which included UV, IR, HRESIMS and NMR experiments.